Homozygous transgenic plants regenerated from rice pollen derived callus via Agrobacterium tumefaciens - FU Ya-ping; SI Hua-min; ZHU Zheng-ge; HU Guo-cheng; SUN Zong-xiu (浙江大学学报. 农业与生命科学版, 2001)
Maize transposable element Ds was inserted into pollen derived calli of Zhonghua 11 (Oryza sativa L. subsp. japonica) mediated by Agrobacterium tumefaciens. The plasmid T-DNA contained a hygromycin-resistance gene (Hpt) and a PPT-resistant gene (Bar) as the selection markers. Seventeen green transgenic plants were regenerated, including 10 haploid and 7 diploid plants. All of the transgenic plants showed the resistance to herbicide BASTA, and the T1 lines from diploid plants also resisted to BASTA without segregation within each line, which indicated that foreign gene was homozygous in diploid transgenic lines. PCR and Southern blot analysis indicated that Bar gene did insert in genomic DNA of Zhonghua 11. The approaches to obtain transgenic homozygous lines are discussed.